ENGLISH FOREIGN LANGUAGE INSTRUCTION: HOW FAR DO WE GO? - Putu Kerti Nitiasih (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This paper reviews some phenomenon on English Language Teaching Instruction. A reflection on the ELT method, material development and production, classroom management and assement were used as the basis to shape a new trends in English Language Teaching Instruction. This paper gives an insight to English Foreign Language Teacher which becames a direction to go after a reflection was done. Trends offer by this article guides the English Foreign Language Teacher to a more-innovative way in EFL instructions.